STRATEGI PEMASARAN PRODUK TABUNGAN HAJI BANK MEGA SYARIAH DI WILAYAH KERJA KANTOR KEMENTERIAN AGAMA KABUATEN LOMBOK TIMUR - Maas Sabirin (Nusantara Hasana Berdikari, 2022)
The general purpose of this study is to find out how the strategies and constraints for marketing Hajj savings products at Bank Mega Syariah in the Office of the Ministry of Religion, East Lombok Regency. The type of research in this research is field research using a qualitative approach. In the process of collecting data in this study, researchers used the methods of observation, interviews, and documentation. The results of the study conclude that the marketing of Hajj savings products by Bank Mega Syariah East Lombok Sub-Branch Office is carried out through 4 (four) strategies, namely: 1) product strategy, consisting of providing security, transactions throughout the bank network, competitive profit sharing, automatic zakat deductions. , connected directly to the Ministry of Religion, and free of administration fees, 2) pricing strategy, by setting a standard price starting from the smallest price, which is Rp. distribution strategy, which is carried out by inviting Muslims, which is carried out by delivering products at several strategic places, and 4) promotion strategy, which is carried out through direct offers, making brochures and banners, inviting Muslims, and opening a booth every week . Meanwhile, the obstacles in marketing the Hajj savings products of Bank Mega Syariah East Lombok Sub-Branch Office are divided into two, namely internal and external constraints. Internal constraints, consisting of: HR problems, technical, legal/structural problems, and market/communal constraints. Meanwhile, external constraints, namely the Covid-19 pandemic which caused limited space for marketing, as well as the cancellation of the departure of Hajj pilgrims which then caused people's reluctance to use Hajj savings products.